Enhanced Fluorescence of N-Acetyl-β-D-Glucosaminidase Activity by ZnO Quantum Dots for Early Stage Mastitis Evaluation - Nirala, Narsingh R.; Shtenberg, Giorgi (Frontiers in Chemistry, 2019)
Recurrent mastitis events are the major cause of annual revenue losses in the dairy sector resulting in decreased milk yield, escalading treatment costs and increased health risk of the entire herd. Upon udder inflammation, several biomarkers are proportionally secreted to its severity onto the blood circulation and consequently into milk (upon breached blood-milk barrier). N-acetyl-β-D-glucosaminidase activity is widely used mastitis indicator in milk, offering simple means of differentiation between healthy quarters from those with subclinical or clinical severity. Herein, we demonstrate fluorescence signal amplification concept for sensitive clinical status discrimination. Tetraethyl orthosilicate coated zinc oxide quantum dots were employed within the conventional N-acetyl-β-D-glucosaminidase activity assay. Under the experimental conditions, a profound non-radiative energy transfer occurred between quantum nanomaterials onto enzymatic fluorescent products resulting in intensified emission of the latter, over 11-folds, in comparison to nanoparticle-free assay. Overall, the fluorescence intensities were proportionally related to zinc oxide quantum dots surface coverage and concentration, SCC values and influenced by the causing bacteria (i.e., Streptococcus dysgalactiae and Coagulase-negative Staphylococci). Finally, the presented proof-of-concept offers an efficient, simple, cost-effective fluorescence signal amplification for early stage mastitis identification, offering means to diagnose the severity of the associated diseases and hence deducing on animals’ clinical status.